Knowledge Level towards Cervical Cancer Among Students of Baabul Kamil Vocational High School - Windi Nurdiawan; Chrestella Odillia; Monica Risnadena Priyas; Yosefa Resti Radinda; Nabila Alifia Ahmad; Nur Agustina Ningsih; Qhonita Anif Febian; Andri Rezano (Global Medical & Health Communication (GMHC), 2020)
Cervical cancer is one of the most common causes of cancer-related death in women worldwide that is mostly preventable and treatable. Knowledge and awareness of cervical cancer screening programs allow the implementation of the prevention of cervical cancer. The community service program is aimed to increase the knowledge of adolescents about cervical cancer and its screening. It was a one-group pretest-posttest quasi-experimental study to measure the level of knowledge of 45 female students of Baabul Kamil Vocational High School, Jatinangor, Sumedang. The study was conducted in May–June 2018. The participants were asked 15 questions, which was an adaptation of previous questionnaires. The program was managed by a mini-lecture that focuses on cervical cancer risk factors and early detection. Furthermore, pretest and posttest were conducted to analyze the level of knowledge on the aforementioned aspects before and after the dissemination descriptively. The participants included in this study were mostly 16 years old (67%). The average recognition of cervical cancer and its early detection was not high. The knowledge of cervical cancer among students of Baabul Kamil Vocational High School was found to be moderate. There is a significant improvement in knowledge level after dissemination. The efficacy of dissemination among female students at Baabul Kamil Vocational High School was apparent in knowledge change. However, good cancer awareness, especially cervical cancer, needs to be established and integrated through effective cancer educational programs in the school curriculum. Key intervention strategies are required to raise cancer awareness in support of taking precautions and early detection measures. TINGKAT PENGETAHUAN SISWI SMK BAABUL KAMIL TENTANG KANKER SERVIKSKanker serviks merupakan salah satu penyebab paling umum kematian terkait kanker pada wanita di seluruh dunia yang sebagian besar dapat dicegah dan diobati. Pengetahuan dan kesadaran tentang program deteksi dini kanker serviks merupakan upaya pencegahan kanker serviks. Program pengabdian pada masyakat ini bertujuan meningkatkan pengetahuan remaja mengenai kanker serviks dan deteksi dininya. Penelitian ini merupakan penelitian one-group pretest-posttest quasi-experimental untuk mengukur tingkat pengetahuan 45 siswi SMK Baabul Kamil, Jatinangor, Sumedang. Penelitian ini dilaksanakan pada bulan Mei–Juni 2018. Responden diberikan 15 pertanyaan yang merupakan adaptasi dari kuesioner sebelumnya. Program ini dilakukan melalui penyuluhan tentang faktor risiko kanker serviks dan deteksi dininya. Selanjutnya, dilakukan pretest dan posttest untuk menganalisis tingkat pengetahuan aspek-aspek tersebut sebelum dan sesudah penyuluhan secara deskriptif. Responden yang terlibat dalam penelitian ini sebagian besar berusia 16 tahun (67%). Identifikasi pengetahuan tentang kanker serviks dan deteksi dininya rerata tidak tinggi. Pengetahuan tentang kanker serviks di kalangan siswa SMKBaabul Kamil tergolong sedang. Terdapat peningkatan yang bermakna tingkat pengetahuan responden setelah diberikan penyuluhan Efektivitas sosialisasi di kalangan siswa perempuan di SMK Baabul Kamil terlihat dari perubahan pengetahuan. Namun, kesadaran kanker yang baik, khususnya deteksi dini kanker serviks perlu diatur dan diintegrasikan melalui program pendidikan kanker yang efektif dalam kurikulum sekolah. Langkah strategis diperlukan untuk meningkatkan kesadaran tentang kanker demi mendukung tindakan pencegahan dan deteksi dini.